Analisis Yuridis Penyerahan Protokol Notaris Oleh Ahli Waris Dengan Lewatnya Batas Waktu kepada Notaris Penerima Protokol (Jurnal Hukum Magnum Opus, 2002)
Notaries play an important role for the parties in making agreements based on civil law. In carrying out its role, a notary is obliged to emphasize the principles of thoroughness and prudence, to ensure justice without discrimination, thereby providing legal certainty and protection of the rights of interested parties. In accordance with the provisions of Article 63 of the Law of the Republic of Indonesia Number 2 of 2014 concerning amendments to Law Number 30 of 2004 concerning the Position of a Notary (hereinafter referred to as Law No. 2/2014 in conjunction with Law No. 30/2004) only stipulates the deadline for submission. However, there is no legal certainty regarding the procedure for submitting the protocol that is carried out after the deadline, there are no arrangements related to the legal consequences of the Notary protocol if it is submitted after the deadline and there are no sanctions for heirs for the late submission of the Notary protocol. This article aims to find out and further analyze the legal consequences of the Notary protocol if it is submitted more than 30 (thirty) days after the Notary's death and sanctions for heirs related to the late deadline for submitting the protocol to the Notary receiving the protocol. Departing from these provisions, legal problems arise, namely: what are the legal consequences for the Notary protocol if it is submitted more than 30 (thirty) days after the Notary's death and whether the heirs can be subject to sanctions related to the passing of the deadline for submitting the protocol of the Deceased Notary. The type of research used to achieve the objectives of this legal research uses normative juridical legal research due to the absence of norms. The results showedthat the submission of the Notary protocol with the passing of the deadline resulted in several legal consequences, namely uncertainty regarding the storage of the protocol of the deceased Notary, damage to the protocol that resulted in losses for the parties and uncertainty related to liability for the issuance of a copy of the minuta deed, therefore, arrangements regarding sanctions for the heirs of the Notary to ensure legal certainty which is clear and konstan. The heirs of the Notary May be sanctioned, if they commit unlawful acts and harm the parties. The sanctions that can be imposed on the heirs for the passage of the deadline for the delivery of the protocol are administrative sanctions in the form of fines in accordance with the losses suffered by the parties, because they are related to administrative disciplinary measures thus, it is necessary to play a proactive role from the Regional Supervisory Assembly in assisting the heirs in carrying out the process of submitting the protocol of the Deceased Notary but on the other hand related to the sanctions given to the heirs in the event of damage and loss of part or all of the Notary protocol, civil sanctions and criminal sanctions, where the heirs abandon the inheritance of the heir in the form of a Notary protocol which should be handed over to the Notary Protocol receiver. Keywords: notary heirs; notary protocol submission; past the deadline; protocol recipient notary Abstrak Notaris berperan penting bagi para pihak dalam pembuatan perjanjian bersumber pada hukum perdata. Dalam menjalankan peranannya, notaris wajib menekankan prinsip ketelitian serta kehati-hatian, untuk menjamin keadilan tanpa diskriminasi, sehingga memberikan kepastian hukum dan perlindungan hak asasi para pihak yang berkepentingan. Sesuai dengan ketentuan Pasal 63 Undang-Undang Republik Indonesia Nomor 2 Tahun 2014 tentang perubahan atas Undang-Undang Nomor 30 Tahun 2004 tentang Jabatan Notaris (selanjutnya disebut UU No. 2/2014 jo UU No. 30/2004) hanya mengatur batas waktu penyerahannya saja, akan tetapi belum ada kepastian hukum mengenai prosedur penyerahan protokol yang dilakukan lewat batas waktu, tidak adanya pengaturan terkait dengan akibat hukum protokol Notaris apabila diserahkan dengan lewat batas waktu dan tidak adanya sanksi bagi ahli waris atas lewatnya batas waktu penyerahan protokol Notaris tersebut. Artikel ini, bertujuan untuk mengetahui dan menganalisis lebih lanjut terkait dengan akibat hukum terhadap protokol Notaris apabila diserahkan lebih dari 30 (tiga puluh) hari semenjak Notaris meninggal dunia serta sanksi bagi ahli waris terkait lewatnya batas waktu penyerahan protokol kepada Notaris penerima protokol. Bertolak dari ketentuan tersebut, maka timbul masalah-masalah hukum yaitu: apa akibat hukum terhadap protokol Notaris apabila diserahkan lebih dari 30 (tiga puluh) hari semenjak Notaris meninggal dunia dan apakah ahli waris dapat dikenai sanksi terkait lewatnya batas waktu penyerahan protokol Notaris yang telah meninggal dunia. Jenis penelitian yang digunakan untuk mencapai tujuan dari penelitian hukum ini menggunakan penelitian hukum yuridis normatif karena adanya kekosongan norma. Hasil penelitian menunjukkan bahwa penyerahan protokol Notaris dengan lewatnya batas waktu menghasilkan beberapa akibat hukum, yaitu ketidakpastian perihal penyimpanan protokol Notaris yang telah meninggal dunia, kerusakan pada protokol yang mengakibatkan kerugian bagi para pihak dan ketidakpastian terkait dengan pertanggungjawaban atas penerbitan salinan minuta akta maka dari itu, diperlukan adanya pengaturan mengenai sanksi bagi ahli waris Notaris untuk menjamin kepastian hukum yang jelas dan konstan. Ahli waris Notaris dapat diberi sanksi, apabila melakukan perbuatan melawan hukum dan merugikan para pihak. Sanksi yang dapat dikenakan kepada ahli waris atas lewatnya batas waktu penyampaian protokol tersebut adalah sanksi administratif berupa denda sesuai dengan kerugian yang diderita para pihak, karena berkaitan dengan penertiban administratif sehingga, perlu peran proaktif dari Majelis Pengawas Daerah dalam membantu ahli waris dalam melakukan proses penyerahan protokol Notaris yang telah meninggal dunia namun disisi lain terkait dengan sanksi yang diberikan kepada ahli waris apabila terjadi kerusakan dan hilangnya sebagian atau seluruh protokol Notaris maka sanksi perdata serta sanksi pidana, yang mana ahli waris menelantarkan harta peninggalan pewaris berupa protokol Notaris yang harusnya diserahkan kepada Notaris Penerima protokol. Kata kunci : ahli waris notaris; lewatnya batas waktu; notaris penerima protokol; penyerahan protokol notaris